Photoinduced charge separation and recombination under distance, orientation, and spin controlled conditions - Jan W. Verhoeven; Michael N. Paddon-Row (International Journal of Photoenergy)
Great efforts have been made to mimic the efficient photoinduced charge separation and concomitant energy storage of natural photosynthetic systems via artificial (supra) molecular constructs as well as to design molecules with potential use for application in molecular electronic circuits. Close packing of such molecules introduces the problem of short-circuiting and cross talk between the separate molecular components. In the present paper the limits will be investigated to which such short-circuiting can be prevented by the use of saturated hydrocarbon (alkane) type insulating structures. Furthermore, as will be shown, several typically molecular scale operating principles such as orbital symmetry and spin multiplicity control can allow the realisation of systems in which fast and efficient charge separation is combined with very slow charge recombination even when the distance between the D(onor) and A(cceptor) moieties is very small.